Uji Hedonik Brownies Kukus Subtitusi Tepung Mocaf - Bijaksana Tanjung; Sulih Wahyudiono Sulih (Eduturisma, 2025)
Steamed brownies are a popular type of cake in Indonesia that are favored for their soft texture and distinctive chocolate flavor. However, using wheat flour as the main ingredient has limitations, especially for those with gluten intolerance. This research was conducted to find alternative raw materials by utilizing modified cassava flour (Mocaf) as a substitute for wheat flour in making steamed brownies. The main issue of this study is how the substitution of wheat flour with Mocaf flour at 25%, 50%, and 75% affects sensory characteristics including color, texture, aroma, and taste, as well as the level of acceptance among respondents. The goal of this research is to determine respondents' preference levels for steamed brownies with Mocaf flour substitution at three different percentages, as well as to identify the best percentage that can be an alternative for gluten-free brownie products, and the method used in this study is experiment with a trial of making brownies based on a modified standard recipe. The research was conducted through hedonic testing with 50 respondents from the Hospitality students of Universitas Asa Indonesia, using a rating scale of 1 - 5 (very dislike to very like). The results showed that all brownie samples with Mocaf substitution received a mean score above 4, which means they were liked to very much liked by the respondents. The formulation with 25% Mocaf substitution had a texture closest to standard brownies, while 50% Mocaf substitution provided a good balance of flavor, aroma, texture, and taste. This innovation is expected to enrich product variety brownies, providing gluten-free food and supporting the utilization of local food ingredients such as cassava.